Managing A Patient With Traumatic Glaucoma: A Case Study - Astari, Dewanti Widya (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2022)
Introduction: Glaucoma condition caused by blunt trauma is a rare case. We report a case study in a patient with secondary glaucoma at a tertiary referral hospital. Case Presentation: A 47-year-old man with chief complaint of pain in the left eye accompanied by headache, with a pain scale of 7/10. The client had a history of being hit while playing badminton. Vital signs are in stable condition. The visual acuity of the right eye was 0.05 and the visual acuity of the left eye was 1/300. Intraocular pressure of the left eye was 46 mmHg. Anterior segment showed conjunctival hyperemia, corneal edema and decrease of pupillary reflex of the left eye. The client complains that he is worried about his condition. Outcome: Nursing care provided to patients with glaucoma focuses on pain and anxiety. The nursing interventions provided are pain management and anxiety reduction. Conclusion: Appropriate nursing care can overcome the worsening of the condition of damage to the internal organs of the eye that can lead to blindness. The family support system is an important part in dealing with the condition of the disease.